Building brand loyalty through community - Sjuchro, Dian Wardiana; Surachman, Akhmad Yani; Dahana, Wirawan Dony; Nurfauziah, Isni (PRofesi Humas, 2025)
Background: Brand loyalty may be more fluid in the digital era. Consumers can easily switch to another brand if they find a product with better reviews or a more attractive offer. Brand loyalty can be built or maintained through online brand communities with a social capital approach. Purpose: The study aimed to describe brand loyalty building through communities. Methods: It used a descriptive qualitative approach to gain deeper insights. Data were collected from relevant academic journals, scientific magazines, previous research results, books, industry magazines, and various newspapers. The data analysis consisted of three streams of activities: data reduction, data presentation, and conclusion drawing/verification to ensure accuracy.  Results: The study results illustrated that brand loyalty can be effectively built, maintained, and improved through well-established brand communities that meet the essential elements of shared language, shared vision, reciprocity, and social trust, fostering deeper connections among members. Conclusion: A credible brand community will encourage consumers and potential consumers to constantly build and improve long-term relationships to interact so that the brand community can transfer brand knowledge to them. Implications: A credible brand community can be built after fulfilling the elements of shared language, shared vision, reciprocity, and social trust – critical factors in increasing brand loyalty behavior.